Dongeng I Dempu Awang dan Cerita Pantun Lutung Kasarung Kajian Sastra Bandingan Nusantanra - Wahyu Sudhiatmika, Ida Bagus; Windhu Sancaya, IDG. (Humanis, 2018)
The research tales of I Dempu Awang and Pantun Lutung Kasarung the analysis Nusantara comparative literature much interested on its, because in between both tales were likely similar. I Dempu Awang explained the adventure of the prince looking for a lady, and Lutung Kasarung describe the god search a lady, they found a lot of problems and obstacles, than the god and the prince transformed their self to be monkeys. These research using comparative literature theory by Robert Clements base on the theme and mythos. The method and technique are as follows: 1) step of providing data, using method of reading, supported by recording technique and translation technique; 2) step of analysis data, using method of qualitative, supported by descriptive comparative technique; 3) step of result data presentation, supported by inductive technique and deductive technique. The result of research of both tales have the similar theme and mythos, and both of the tales found motive of Panji. The end of analysis Nusantara comparative literature could donate to compile the history of Bali literature.